Yeast ADP/ATP carrier (AAC) proteins exhibit similar enzymatic properties but their deletion produces different phenotypes - Drgon, T; Sabová, L; Gavurniková, G; Kolarov, J (FEBS letters, 1992)
Saccharomyces cerevisiae strains expressing a single type of ADP/ATP carrier (AAC) protein were prepared from a mutant in which all AAC genes were disrupted, by transformation with plasmids containing a chosen AAC gene. As demonstrated by measurements of [14C]ADP specific binding and transport, all three translocator proteins, AAC1, AAC2 and AAC3 when present in the mitochondrial membrane, exhibited similar translocation properties. The disruption of some AAC genes, however, resulted in phenotypes indicating that the function of these proteins in whole cells can be quite different. Specifically, we found that the disruption of AAC1 gene, but not AAC2 and AAC3, resulted in a change in colony phenotype.
Keywords: adenosindifosfát; Saccharomyces cerevisiae; Mitochondria; Transformation, Genetic; DNA Mutational Analysis; Kinetics; Phenotype; transformace genetická; mitochondriální ADP/ATP-translokasy; Adenosine Diphosphate; mitochondrie; Mitochondrial ADP, ATP Translocases; fenotyp; kinetika; mutační analýza DNA